Facilitating future implementation and translation to clinical practice: The Implementation Planning Assessment Tool for clinical trials - Christine P. Kowalski; Linda M. Kawentel; Tassos C. Kyriakides; Lori Davis; Nicholas W. Bowersox; Amy M. Kilbourne; Grant D. Huang; Andrea L. Nevedal (Journal of Clinical and Translational Science, 2022)
Implementation assessment plans are crucial for clinical trials to achieve their full potential. Without a proactive plan to implement trial results, it can take decades for one-fifth of effective interventions to be adopted into routine care settings. The Veterans Health Administration Office of Research and Development is undergoing a systematic transformation to embed implementation planning in research protocols through the Cooperative Studies Program, its flagship clinical research program. This manuscript has two objectives: 1) to introduce an Implementation Planning Assessment (IPA) Tool that any clinical trialist may use to facilitate post-trial implementation of interventions found to be effective and 2) to provide a case study demonstrating the IPA Tool’s use. The IPA Tool encourages study designers to initially consider rigorous data collection to maximize acceptability of the intervention by end-users. It also helps identify and prepare potential interested parties at local and national leadership levels to ensure, upon trial completion, interventions can be integrated into programs, technologies, and policies in a sustainable way. The IPA Tool can alleviate some of the overwhelming nature of implementation science by providing a practical guide based on implementation science principles for researchers desiring to scale up and spread effective, clinical trial-tested interventions to benefit patients.